2021
DOI: 10.1111/ppl.13387
|View full text |Cite
|
Sign up to set email alerts
|

Redox imbalance impedes photosynthetic activity in rice by disrupting cellular membrane integrity and induces programmed cell death under submergence

Abstract: Climate change negatively impacts the global hydrological resources leading to detrimental flood events. Submergence impedes the cellular membrane integrity, consequently affecting the membrane fluidity. Different abiotic stresses influence membrane lipid composition. Therefore, the remodeling of membrane lipids plays a major role in stress adaptation. Submergence-induced membrane lipid peroxidation is well established in plants. However, dynamic changes in lipid composition for regulating submergence toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Li and Li (2018) found that the soluble sugar content in the stem of bermudagrass was also significantly decreased under shallow submergence (above the soil 10 cm) and under deep submergence (above the soil 2 m) [ 17 ], whereas the soluble sugar content in the root of bermudagrass increased under shallow submergence and decreased under deep submergence. Meanwhile, due to the low-oxygen content and slow diffusion rate in the flooding environment, aerobic respiration of plants becomes limited [ 18 , 19 , 20 ], which results in a limited supply of energy for nutrient uptake and transport [ 21 ]. A former study documented that ethanol dehydrogenase activity in bermudagrass roots increased under submergence and increased submergence depth [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li and Li (2018) found that the soluble sugar content in the stem of bermudagrass was also significantly decreased under shallow submergence (above the soil 10 cm) and under deep submergence (above the soil 2 m) [ 17 ], whereas the soluble sugar content in the root of bermudagrass increased under shallow submergence and decreased under deep submergence. Meanwhile, due to the low-oxygen content and slow diffusion rate in the flooding environment, aerobic respiration of plants becomes limited [ 18 , 19 , 20 ], which results in a limited supply of energy for nutrient uptake and transport [ 21 ]. A former study documented that ethanol dehydrogenase activity in bermudagrass roots increased under submergence and increased submergence depth [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane stability index (MSI) was calculated following the equation proposed by Basu et al (2021a).…”
Section: Determination Of Electrolyte Leakage and Membrane Stability ...mentioning
confidence: 99%
“…Accumulation of superoxide anion ( • O 2 − ), singlet oxygen (O 2 * ), hydrogen peroxide (H 2 O 2 ), hydroxide ion (OH − ) induced by water stress triggers membrane lipid peroxidation and cell death (Basu et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Plant extract containing equal concentrations of proteins were run on SDS-PAGE along with a pre-stained marker (Basu et al 2021). The proteins were blotted with trans-blot membrane (Bio Rad) followed by blocking with skimmed milk.…”
Section: Western Blottingmentioning
confidence: 99%